Vampire diaries : The Return - Smith, L. J. (Lisa J.) (Vampire diaries, 2009)
A continuation of "The Vampire Diaries" series in which Elena returns to life after sacrificing herself to save the two vampire brothers who love her and finds she now has powerful gifts that once more put her in the middle of a battle between Damon and Stefan.